Trends of Microsurgical Head and Neck Free Flap Reconstruction and Safety during the COVID-19 Pandemic - Bustos, Valeria P.; Elmer, Nicholas; Veeramani, Anamika; Comer, Carly D.; Kinney, JacqueLyn R.; Manstein, Samuel M.; Hassell, Natalie; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery Open, 2024)
Background The coronavirus disease 2019 (COVID-19) pandemic poses unprecedented challenges among patients with head and neck (HN) cancer that require oncological and reconstructive surgeries. This study aims to identify differences in postoperative outcomes for patients who underwent microsurgical HN free flap reconstruction prior to versus during the COVID-19 pandemic.Methods A retrospective observational study using the American College of Surgeons National Surgical Quality Improvement Program 2019 to 2020 database to identify patients with HN cancer who underwent a vascularized free tissue transfer was undertaken. Two cohorts were created: pre- and during COVID-19. Fisher's exact test and the unpaired Student's t-test were used to evaluate differences in sociodemographic and clinical characteristics between the cohorts. Multivariable logistic regression was used to assess differences in reoperation rates between groups as well as to identify potential risk factors for reoperation.Results A total of 763 patients were analyzed. The mean age of patients in the overall cohort was 63.6 (standard deviation: 11.5) years. Most patients were white (62.7%). Overall, no statistically significant difference was evidenced between cohorts in terms of immediate postoperative outcomes. Similarly, reoperation rates were similar between groups (p > 0.05). Dependent functional status (p = 0.021) and postoperative infection (p < 0.001) were found to be risk factors for reoperation after holding other factors constant.Conclusion HN flap reconstruction can be performed safely during the COVID-19 era. Standardized protocols for patient selection must be strictly followed to avoid disease progression and optimize surgical outcomes. Further studies assessing long-term outcomes during the pandemic are of utmost importance to elucidate the true impact of the COVID-19 pandemic on this population.
Keywords: reconstruction; microsurgery; head and neck; COVID-19